Summer and Winter Effect of Innovative Cool Roof Tiles on the Dynamic Thermal Behavior of Buildings - Anna Laura Pisello; Federico Rossi; Franco Cotana (Energies, 2014)
Cool roofs represent an acknowledged passive cooling technique to reduce building energy consumption for cooling and to mitigate urban heat island effects. This paper concerns the evaluation of the dynamic effect of new cool roof clay tiles on building thermal performance in summer and winter conditions. To this end, these properties have been analyzed on traditional roof brick tiles through an indoor and outdoor two-year long continuous monitoring campaign set up in a residential building located in central Italy. The analysis and the cooperation with industrial companies producing brick tiles and reflective coatings allowed the production of a new tile with notable “cool roof” properties through the traditional industrial manufacturing path of such tiles. Notable results show that during summer the high reflection tiles are able to decrease the average external roof surface temperature by more than 10 °C and the indoor operative temperature by more than 3 °C. During winter the average external surface temperature is lower with high reflection tiles by about 1 °C. Singular optic-thermal phenomena are registered while evaluating the dynamics of the cool roof effect. Interesting findings show how the sloped cool roof application could suggest further considerations about the dynamic effect of cool roofs.